Editorial Guidance. Guidelines to Authors - Sociedad, Salud y (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2015)
"Salud y Sociedad Uptc" is the official scientific journal of the School of Health Sciences of the "Universidad Pedagógica y Tecnológica de Colombia". This journal publishes biannually original manuscripts from the health and psychology fields. The main objective of this journal is publishing original research work and other types of scientific papers that help expand the knowledge and promote the advancement of the health sciences. Therefore this publication is targeted to health and psychology professionals, researchers of the health sciences, students, and all of those involved in the practice of health and psychology related activities. The types of publications offered by the journal are: original papers, peer reviews, reflective pieces, short articles, essays, clinical cases, and letters to the editor. Under the principle of globalization of knowledge, this journal offers open access of its contents through its website.